2007
DOI: 10.21273/hortsci.42.3.596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Susceptibility of Carnation Cultivars to Fusarium Wilt and Determination of Fusarium oxysporum fsp. dianthi Races in Southwest Spain

Abstract: Eighteen commercial cultivars of carnation were inoculated with eight isolates of F. oxysporum fsp. dianthi (Fod) from a collection of isolates obtained from diseased plants surveyed in the main growing area of Spain. Susceptible reactions were shown in most cultivars inoculated with six isolates characterized as race 2 when tested on differentials. However, cultivars Elsy and Westcristal were fully resistant to the six is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…Susceptible cultivars suffer severe yield losses, and considerable yield losses are also common in carnation cultivars previously described as resistant (Prados-Ligero et al 2007). The crop is mainly produced as a monoculture in greenhouses; rooted cuttings are planted in late spring (May to June) and removed after 22 to 23 months before preparation of the soil for new plantings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptible cultivars suffer severe yield losses, and considerable yield losses are also common in carnation cultivars previously described as resistant (Prados-Ligero et al 2007). The crop is mainly produced as a monoculture in greenhouses; rooted cuttings are planted in late spring (May to June) and removed after 22 to 23 months before preparation of the soil for new plantings.…”
Section: Introductionmentioning
confidence: 99%
“…The crop is mainly produced as a monoculture in greenhouses; rooted cuttings are planted in late spring (May to June) and removed after 22 to 23 months before preparation of the soil for new plantings. Consequently, populations of soilborne plant pathogens often increase to unacceptable levels (Prados-Ligero et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, R2 isolates from Italy, all of them in the R2I race group, seem to be molecularly different from the Spanish R2I isolates, because most of them amplify the R2II-associated specific amplicons with the SCAR primers. Results of Prados-Ligero et al (2007), testing the resistance of different carnation cultivars inoculated with Italian isolates of Fod, demonstrated that different isolates of the same race (R1 or R2) caused different reactions (R or S) on the same cultivar, thus suggesting the existence of pathogenic/genetic diversity in races R1 and R2 from Italy. Our results support this hypothesis and demonstrate that genetic diversity exists at least within race 1 isolates from Italy.…”
Section: R1mentioning
confidence: 99%
“…Soil populations of Fod can be highly diverse, even within a single soil, and the knowledge of this diversity is essential for the choice of suitable resistant carnation cultivars in specific growing areas. In fact, recent observations have shown that considerable yield losses are becoming common in carnation cultivars previously described as resistant to fusarium wilt (Prados-Ligero et al 2007). …”
mentioning
confidence: 99%
“…The forma specialis dianthi (Fod) causes Fusarium wilt of carnation (Dianthus caryophyllus L.), a disease that is responsible for severe losses in areas where this flower is grown. The pathogen is widespread in soils worldwide [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%